2022
DOI: 10.1371/journal.pone.0278145
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of emerging inflammatory markers for predicting oxygen support requirement in COVID-19 patients

Abstract: Coronavirus disease 2019 (COVID-19), a highly contagious pathogenic viral infection caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has spread rapidly and remains a challenge to global public health. COVID-19 patients manifest various symptoms from mild to severe cases with poor clinical outcomes. Prognostic values of novel markers, including neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR) and C-reactive protein to lymphocyte ratio (CLR) calculated from routine l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…A high NLR in early AHRF indicates the severity of the disease and organ dysfunction and has been observed in several conditions associated with tissue damageinduced systemic inflammatory response syndrome [21]. Although several studies and our data have demonstrated that HFNC treatment failure certainly has a higher NLR [18,20,22], the cut-off NLR value to determine HFNC treatment outcomes requires further examination. Other factors, such as pH, CO 2 levels in VBG, BUN, creatinine, and albumin levels, were not different between the two groups.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…A high NLR in early AHRF indicates the severity of the disease and organ dysfunction and has been observed in several conditions associated with tissue damageinduced systemic inflammatory response syndrome [21]. Although several studies and our data have demonstrated that HFNC treatment failure certainly has a higher NLR [18,20,22], the cut-off NLR value to determine HFNC treatment outcomes requires further examination. Other factors, such as pH, CO 2 levels in VBG, BUN, creatinine, and albumin levels, were not different between the two groups.…”
Section: Discussionmentioning
confidence: 63%
“…The NLR is considered a potential marker for predicting the requirement of a high-flow oxygen nasal cannula and invasive mechanical ventilation in acute hypoxemic respiratory cases [18][19][20]. A high NLR in early AHRF indicates the severity of the disease and organ dysfunction and has been observed in several conditions associated with tissue damageinduced systemic inflammatory response syndrome [21].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that CRP and novel markers such as CRP-to-lymphocyte ratio (CLR), neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) can all predict oxygen requirement in COVID-19 patients [ 20 ]. However, missing from the literature until now has been an adjudication of the relative performance of LCR as compared to CRP for predicting mortality and other serious adverse outcomes (such as intubation and ICU requirement) in acute COVID-19; this study provides such head-to-head comparison.…”
Section: Discussionmentioning
confidence: 99%